ANCAR Mobile App User Manual - Akshatha, Annaiah (2023)
AICCRA-ANCAR is an android-based mobile application that is exclusively developed to capture information on training, capacity development (CapDev), and extension activities performed in eight Agro ecological zones (AEZ) of Senegal. The app enables the ANCAR agents to collect vast information on meetings & workshops, training & visits, data on intermediates, technology transfers, details on the dynamics of the organization, data on providing management advice to farmers, and information on research & development in the project programs. This app is available in both English & French versions for the users. The data collected via mobile app is uploaded to a cloud-based system in real-time and presented on a web-based dashboard. The app is designed to minimize unintentional data collection errors and to hasten data analysis in which data will be more presentable and understandable. The development and deployment of the mobile app have been supported by the National Consulting Agency Agricultural and Rural (ANCAR) & CGIAR - AICCRA project.